2017
DOI: 10.5194/os-13-443-2017
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of basin dynamics on the regional sea level rise in the Black Sea

Abstract: Abstract. Satellite altimetry measurements show that the magnitude of the Black Sea sea level trends is spatially uneven. While the basin-mean sea level rise from 1993 to 2014 was about 3.15 mm yr −1 , the local rates of sea level rise varied from 1.5-2.5 mm yr −1 in the central part to 3.5-3.8 mm yr −1 at the basin periphery and over the northwestern shelf and to 5 mm yr −1 in the southeastern part of the sea. We show that the observed spatial differences in the dynamic sea level (anomaly relative to the basi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
12
0
2
Order By: Relevance
“…The obtained results can characterize the mixing processes for the entire sea, since in January -March a single cyclonic circulation of water masses is observed [5]. This cyclonic circulation of the upper layer is determined by the surface wind stress curl, the main contribution to which is made by monsoon and orographic effects [16][17][18].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results can characterize the mixing processes for the entire sea, since in January -March a single cyclonic circulation of water masses is observed [5]. This cyclonic circulation of the upper layer is determined by the surface wind stress curl, the main contribution to which is made by monsoon and orographic effects [16][17][18].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…In the Rim Current northern branch, where the seasonal thermocline upper boundary was located at about 40 m depth, the variation of thermocline and CIL location depths significantly depended on the fluctuations of the surface current. The comparison of average velocity values for December [16][17][18][19][20][21][22][23][24][25][26][27][28]2012 showed that the surface current velocity (V = 0.26 m·s -1 ) was about two times higher than the geostrophic one (V g = 0.14 m·s -1 ). Apparently, this can explain an insignificant correlation of geostrophic velocity with the depth of the seasonal thermocline upper boundary.…”
Section: Variability Of the Upper Mixed Layer (Uml) Average Temperatumentioning
confidence: 99%
“…Полученные результаты могут характеризовать процессы перемешивания для всего моря, поскольку в январемарте наблюдается единое циклоническое вращение водных масс [5]. Эта циклоническая циркуляция верхнего слоя определяется завихренностью касательного напряжения трения приземного ветра, основной вклад в которую дают муссонный и орографический эффекты [16][17][18]. Вообще преобладающее в северной части моря в течение года направление ветра (северное и северо-восточное) формирует циклоническую циркуляцию вод [9], а межгодовая и синоптическая изменчивость циркуляции атмосферы в регионе Черного моря регулирует повторяемость и силу ветра различных румбов в его западной части [2,9].…”
Section: полученные результатыunclassified
“…According to Avsar et al (2015), the rate of rise was 3.2 mm/year with analysis of altimetry data between January 1993 and December 2014. Changes in the budget of water (water balance) are considering as the main reason for the basin-averaged sea level changes in the Black Sea (Ginzburg et al, 2013;Kubryakov et al, 2017;Stanev et al, 2000;Volkov and Landerer, 2015;Yildiz et al, 2011). For example, Ginzburg et al (2013) concluded that the sea level change in 1993-2002 was well correlated with variability of the Danube discharge.…”
Section: Long-term Sea Level Changes In the Black Seamentioning
confidence: 99%